2019
DOI: 10.1007/s11040-019-9307-7
|View full text |Cite
|
Sign up to set email alerts
|

Concentration Behavior and Lattice Structure of 3D Surface Superconductivity in the Half Space

Abstract: We study the three-dimensional Ginzburg-Landau model of superconductivity for strong applied magnetic fields varying between the second and third critical fields. In this regime, it is known from physics that superconductivity should be essentially restricted to a thin layer along the boundary of the sample. This leads to the introduction of a Ginzburg-Landau model on a half-space. We prove that the non-linear Ginzburg-Landau energy on the half-space with constant magnetic field is a decreasing function of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…(2.10) This is a well-known result related to the Landau bands for constant magnetic fields in R 3 (see e.g. [FMP,Proposition 2.1]).…”
Section: 21mentioning
confidence: 78%
See 1 more Smart Citation
“…(2.10) This is a well-known result related to the Landau bands for constant magnetic fields in R 3 (see e.g. [FMP,Proposition 2.1]).…”
Section: 21mentioning
confidence: 78%
“…Within this context, 3D models were also studied in the mathematical literature on unbounded/bounded domains with smooth boundary or having edges [LP2,Pan2,HM2,Pop1,Pop2,Pop3] (also see [FDM,FH3,FH4,FK2,FKP,FMP]). However, all these contributions considered magnetic fields with a constant strength.…”
mentioning
confidence: 99%
“…It is expected that a regime of surface superconductivity with similar features occurs also for genuine 3D samples but so far only partial results are available [38,39]. In particular, in [38,Thm 1.1] (see also [36]) it is shown that such a regime does exist and the leading order term in the energy asymptotics can be identified, although in terms of a rather implicit effective problem.…”
Section: State Of the Artmentioning
confidence: 99%
“…In particular, in [38,Thm 1.1] (see also [36]) it is shown that such a regime does exist and the leading order term in the energy asymptotics can be identified, although in terms of a rather implicit effective problem. In [39,Thm. 1.5] it is then proven that, when the magnetic field is parallel to the 3D boundary, the effective model is still given by the 1D functional (2.3) above.…”
Section: State Of the Artmentioning
confidence: 99%
“…It is known that (see [1][2][3][4][5][6]) at a certain value of the magnetic field strength in superconducting materials of the second kind, a surface superconducting phenomenon occurs. This kind of magnetic field is called the third critical field.…”
Section: Introductionmentioning
confidence: 99%